Analysis of Regional Accounting and Asset Management Information Systems at Local Government - Sangrila Gladys Miracle Blegur (CV. Namora dan Riona Bersaudara, 2026)
This study aims to analyze the implementation of the accounting information system (AIS) in the management of regional assets at the Regional Revenue and Asset Agency (BPAD) of East Nusa Tenggara Province. The research focuses on evaluating the effectiveness of AIS components, including human resources, procedures, data quality, and infrastructure in supporting asset management activities. A qualitative approach was employed using interviews, observations, and document analysis to obtain a comprehensive understanding of the system in practice. The findings indicate that the AIS has generally supported administrative processes and financial reporting by enabling systematic recording and documentation of regional assets. However, the system has not yet achieved optimal effectiveness. The main challenges are related to limited technical competence among employees and inconsistencies in asset data, such as incomplete records and input errors. These issues are largely influenced by the reliance on Microsoft Excel as a temporary system, which lacks integration and automated control features. On the other hand, procedural and infrastructure aspects are relatively well established, as indicated by the availability of standard operating procedures and adequate facilities. The study concludes that improving human resource capacity, strengthening data validation processes, and developing an integrated AIS are essential to enhance the effectiveness, transparency, and accountability of regional asset management.